Influence of Therapy Compliance Using Medication Possession Ratio Method for Patients with Metabolic Syndrome - Christianus H. Setiawan; Phebe Hendra; Dita M. Virginia; Lisa K. Sari (Universitas Padjadjaran, 2022)
Metabolic syndrome is still a major problem in developing countries and it has an association with high blood pressure, blood glucose, and lipid profile abnormalities, which can cause cardiovascular disease. This indicates that it is important to provide adequate treatment, but patient compliance has effects on the outcome. Improving patients’ compliance to treatment can provide a better control of the condition. Therefore, this study aimed to determine the association between medication compliance and the therapeutic outcome of metabolic syndrome. This observational analytic study was conducted using a retrospective cohort design for one year of observation, namely April 2020-March 2021. The influence of patient compliance with therapy outcomes in terms of blood pressure, blood glucose, and lipid profile was assessed using the medication possession ratio method. This study was carried out by examining patients’ medical records from the Bethesda Lempuyangwangi Hospital as parameters for compliance, while the outcome parameters were assessed by experts. The data obtained were analyzed using Anova (homogeneous data) or Kruskal-Wallis (not homogeneous data) to determine the differences in the compliance based on patients’ characteristics. The relationship of adherence to therapeutic outcomes was analyzed using logistic bivariate. From 174 patients’ data that was observed, only 151 had a blood test. The average systolic blood pressure, total cholesterol, triglyceride, and HbA1c levels were above the standard threshold. The three levels of compliance had no significant relationship with blood pressure, HbA1c, and lipid profiles (p>0.05). The adjusted data for age and gender on adherence showed patients with low compliance, and they have a 2.08 times risk of having high triglyceride levels compared to others (p<0.05). The results indicated the patients’ low compliance to therapy, hence, health professionals must strengthen education to improve this condition.Keywords: Blood glucose, blood pressure, compliance, lipid profile, medication possession ratio Pengaruh Ketaatan Terapi menggunakan Metode Medication Possession Ratio pada Penderita Sindrom Metabolik AbstrakSindrom metabolik masih menjadi masalah besar di negara berkembang. Sindrom metabolik berkorelasi dengan tekanan darah tinggi, peningkatan gula darah, dan kelainan profil lipid. Seiring waktu sindrom metabolik akan menyebabkan penyakit kardiovaskular. Terapi yang memadai merupakan hal penting, tetapi seringkali kepatuhan pasien akan memengaruhi hasil terapi. Peningkatan kepatuhan pasien terhadap pengobatan diduga dapat menghasilkan kondisi sindrom metabolik yang lebih baik, sehingga perlu ditentukan hubungan antara kepatuhan pengobatan dan hasil terapi sindrom metabolik. Penelitian ini merupakan penelitian observasional analitik dengan desain kohort retrospektif selama satu tahun (April 2020–Maret 2021). Kami menyelidiki kepatuhan terhadap hasil terapi pasien (tekanan darah, glukosa darah, dan profil lipid) menggunakan metode medication possession ratio. Penelitian dilakukan dengan mengambil rekam medis pasien di RS Bethesda Lempuyangwangi sebagai parameter kepatuhan pasien sedangkan hasil terapi dilihat dari pemeriksaan darah dan pemeriksaan fisik yang dilakukan oleh tenaga ahli. Data yang diperoleh dianalisis menggunakan Anova (data homogen) atau Kruskal-Wallis (data tidak homogen) untuk melihat perbedaan kepatuhan berdasarkan karakteristik pasien. Hubungan kepatuhan terhadap hasil terapi dianalisis menggunakan bivariat logistik. Sebanyak 174 data pasien dikumpulkan dan hanya 151 responden yang datang pada hari pengecekan darah. Rata-rata tekanan darah sistolik, kolesterol total, trigliserida, dan kadar HbA1c pasien berada di atas ambang standar. Tingkat kepatuhan yang terdiri dari 3 tingkatan tidak memiliki hubungan yang signifikan dengan tekanan darah, HbA1c, dan profil lipid (p>0,05). Penyesuaian untuk data usia dan jenis kelamin pada tingkat kepatuhan pada statistik menyatakan pasien dengan kepatuhan rendah memiliki peluang 2,08 kali untuk memiliki kadar trigliserida tinggi dibandingkan pasien dengan kepatuhan tinggi (p<0,05). Hasil penelitan mengindikasikan rendahnya kepatuhan terapi pasien sehingga profesional kesehatan harus memperkuat edukasi untuk meningkatkan kepatuhan pengobatan.Kata kunci: Glukosa darah, kepatuhan, medication possession ratio, profil lipid, tekanan darah